1998
DOI: 10.1016/s0014-5793(98)00671-1
|View full text |Cite
|
Sign up to set email alerts
|

Competitive inhibition analysis of the enzyme‐substrate interaction in the carboxy‐terminal processing of the precursor D1 protein of photosystem II reaction center using substituted oligopeptides

Abstract: A clear parallelism was demonstrated between the efficiency as substrate of the substituted oligopeptides corresponding to the carboxy-terminal (C-terminal) sequence of the precursor D1 protein (pD1) in the in vitro enzymatic assay and their competitive inhibitory capacity toward the proteolytic Cterminal processing of the full-length pD1 integrated in the intact photosystem II complex embedded in the thylakoid membrane of Scenedesmus obliquus LF-1 mutant, as shown e.g. by the influence of L343A, A345G and A34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Exceptional cases are, for examples, Val in Chlorella vulgaris C-27, Gly in Gloeobacter violaceus, Asp in Cyanidium caldarium, and Cys in Gymnodinium mikimotoi. In our analysis using synthetic oligopeptides, either as the substrate or as the competitive inhibitor for the processing of membrane-embedded substrate pD1 of S. obliquus (Yamamoto and Satoh 1998), this position was shown to be crucial to the cleavage efficiency. Furthermore, the competitive mixed-culture experiments using genetically engineered C. reinhardtii (Taguchi et al 1998) showed that cell viability depends on the order of efficiency as the substrate and the competitive inhibitor (Yamamoto and Satoh 1998).…”
Section: Substrate the Precursor D1 Proteinmentioning
confidence: 87%
See 1 more Smart Citation
“…Exceptional cases are, for examples, Val in Chlorella vulgaris C-27, Gly in Gloeobacter violaceus, Asp in Cyanidium caldarium, and Cys in Gymnodinium mikimotoi. In our analysis using synthetic oligopeptides, either as the substrate or as the competitive inhibitor for the processing of membrane-embedded substrate pD1 of S. obliquus (Yamamoto and Satoh 1998), this position was shown to be crucial to the cleavage efficiency. Furthermore, the competitive mixed-culture experiments using genetically engineered C. reinhardtii (Taguchi et al 1998) showed that cell viability depends on the order of efficiency as the substrate and the competitive inhibitor (Yamamoto and Satoh 1998).…”
Section: Substrate the Precursor D1 Proteinmentioning
confidence: 87%
“…However, under the condition where the cleavage reaction takes place, the C-terminal part of pD1, including upstream of the cleavage site, e.g., Asp-342, seems to be exposed to interact with the enzyme in the lumenal space (Bowyer et al 1992;Taguchi et al 1995;Yamamoto and Satoh 1998). This is in contrast to the fact that the mature C-terminus is buried deeply in a crevice between the D1 and CP43 subunits, and beneath Cyt c 550 and PsbU, in the structure of cyanobacterial PS II complex recently elucidated (Loll et al 2005).…”
Section: Substrate the Precursor D1 Proteinmentioning
confidence: 99%
“…The cleavage of peptides was examined by reverse-phase High Performance Liquid Chromatography (HPLC) (model HPX-87P, Bio-Rad, CA, USA). Three oligopeptides were tested for CtpAp cleavage including S-24 (pD1) (Val-Met-His-Glu-Arg-Asn-Ala-His-Asn-Phe-Pro-Leu-Asp-Leu-Ala-Ala-Ile-Glu-Ala-Pro-Ser-Thr-Asn-Gly) corresponding to the C-terminal 24 aa of spinach pD1, as well as N15 (Val-Met-His-Glu-Arg-Asn-Ala-His-Asn-Phe-Pro-Leu-Asp-Leu-Ala) and C9 (Ala-Ile-Glu-Ala-Pro-Ser-Thr-Asn-Gly) [ 45 ]. These oligopeptides were synthesized in Sangon (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…RCII binds four to six chlorophyll a molecules, two pheophytin a molecules, two carotenoids, two quinones, Fe, and Mn. In higher plants, the D1 protein is synthesized as a precursor (pD1), which has a C-terminal extension that is no longer present in the photoactive PSII complex and is known to be cleaved by a luminal peptidase (Erickson and Rochaix, 1992;Yamamoto and Satoh, 1998). Processing of pD1 might influence assembly of the PSII complex, because work with the LF1 mutant of Scenedesmus obliquus , which contains an inactive processing protease (Trost et al, 1997), indicates that the mutant contains assembled and photoactive PSII core complexes but is unable to evolve oxygen (Diner et al, 1988).…”
mentioning
confidence: 99%